Nano photocatalyst, preparation method thereof and application of nano photocatalyst in oil field polymer-containing sewage treatment
By preparing the photocatalyst with Ov-BiOBr nanosheet structure, the problems of poor catalytic performance and insufficient stability of nanophotocatalysts in the prior art are solved, and efficient degradation and photocorrosion resistance of oil fields are achieved, with a wide range of Value of industrial application.
Patent Information
- Application Number
- CN202411413382.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-07
AI Technical Summary
The existing nanophotocatalysts have poor catalytic performance and insufficient stability, and cannot effectively degrade sewage containing oil fields.
By adding bismuth-sourced ethylene glycol solution to an aqueous solution of potassium bromide for hydrothermal reaction, a photocatalyst with Ov-BiOBr nanosheet structure was prepared, which inhibits the direct recombination of photogenerated carriers and improves the separation ability of photogenerated electrons and holes. , and oxygen vacancies are introduced to enhance photocorrosion resistance.
The efficient degradation of polysewage-containing oilfields was achieved, and the removal rate of polyacrylamide reached 96.1%. The catalytic activity remained efficient after 30 reuses, and had good photocorrosion resistance.
Smart Images

Figure CN119386902A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of photocatalysts, and in particular, relates to a nano photocatalyst and a preparation method thereof, and an application thereof in the treatment of polymer-containing wastewater in oil fields. Background Art
[0002] In order to improve the recovery rate of crude oil in oil fields, tertiary oil recovery methods are usually used. In the tertiary oil recovery method, polymer flooding mainly uses polyacrylamide (HPAM) to increase the viscosity of water, thereby reducing the permeability of water and the viscosity difference between oil and water, and then changing the oil-water flow rate to achieve the purpose of improving the recovery rate. However, the polymer-containing wastewater produced by polymer flooding not only increases the difficulty of wastewater treatment, but also causes wear of pipeline equipment and even water source poisoning. Photocatalysis is usually used to degrade polymer-containing wastewater in oil fields, but the performance of the existing photocatalysts is poor and cannot meet large-scale applications. Therefore, it is necessary to develop new catalysts to meet the degradation requirements of polymer-containing wastewater in oil fields.
[0003] Bismuth oxybromide (BiOBr) has a unique layered structure composed of [Bi2O2] plates and dihalogen atom plates, which has good visible light response and high photogenerated electron-hole separation efficiency, making BiOBr materials widely used in the degradation of dyes, various phenols and water pollutants. However, pure BiOBr catalysts have poor absorption capacity for visible light and a wide energy band gap, and cannot produce enough photogenerated carriers to degrade oilfield wastewater containing polymers. Therefore, it is necessary to modify the BiOBr catalyst to meet the requirements for the degradation of oilfield wastewater containing polymers. At present, no treatment of oilfield wastewater containing polymers using modified BiOBr catalysts has been found. Summary of the invention
[0004] The present application discloses a nano photocatalyst and a preparation method thereof, and its application in the treatment of polymer-containing wastewater in oil fields, aiming to solve the technical problems of poor catalytic performance and insufficient stability of existing nano photocatalysts.
[0005] In order to achieve the above purpose, the technical solution of this application is:
[0006] The first aspect of the present application provides a method for preparing a nano photocatalyst, the method comprising:
[0007] The bismuth source ethylene glycol solution is added into the potassium bromide aqueous solution and mixed, and a hydrothermal reaction is carried out at 140-180° C. for 8-20 hours. After separation and collection, a nano photocatalyst is obtained.
[0008] In combination with the first aspect, preferably, the bismuth source is one of bismuth nitrate, bismuth sulfate, bismuth chloride and bismuth bromide.
[0009] In combination with the first aspect, preferably, the bismuth source is bismuth nitrate.
[0010] In combination with the first aspect, preferably, the molar ratio of the bismuth source to potassium bromide is 1:1-1.5.
[0011] In combination with the first aspect, preferably, the temperature of the hydrothermal reaction is 160° C. and the time is 12 h.
[0012] In combination with the first aspect, preferably, the ethylene glycol solution of the bismuth source is added to the aqueous solution of potassium bromide and mixed for 80-100 minutes.
[0013] The second aspect of the present application provides a nano photocatalyst prepared by the preparation method described in the first aspect, wherein the nano photocatalyst is a nano sheet structure.
[0014] The third aspect of the present application provides the use of the nano-photocatalyst described in the second aspect in the treatment of polymer-containing wastewater in oil fields.
[0015] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0016] The preparation method of the nano photocatalyst provided in the present application is prepared by adding a bismuth source ethylene glycol solution to an aqueous solution of potassium bromide for hydrothermal reaction. On the one hand, the nano photocatalyst can inhibit the direct recombination of photogenerated carriers, thereby greatly improving the separation ability of photogenerated electrons and holes, forming hydroxyl radicals and superoxide radicals, and then realizing the efficient degradation of oilfield polymer-containing wastewater; on the other hand, oxygen vacancies can be introduced into the lattice of the compound, so that the Ov-BiOBr nanosheet photocatalyst has anti-photocorrosion performance when degrading oilfield polymer-containing wastewater, and the catalytic activity can still maintain high efficiency after repeated use for 30 times. At the same time, the preparation process of the present application is simple, the conditions are mild, and it is easy to control, and the purity of the product is high, which has a wide range of industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 XRD diagrams of A1-nano photocatalyst and B1-photocatalyst prepared in the examples of the present application;
[0019] Figure 2 The scanning electron microscope images of the A1-nano photocatalyst and the B1-photocatalyst prepared in the examples of the present application;
[0020] Figure 3EPR graphs of A1-nano photocatalyst and B1-photocatalyst prepared in the examples of the present application;
[0021] Figure 4 Solid ultraviolet diffuse reflectance spectra of A1-nano photocatalyst and B1-photocatalyst prepared in the examples of the present application;
[0022] Figure 5 Solid steady-state fluorescence spectra of A1-nano photocatalyst and B1-photocatalyst prepared in the examples of the present application;
[0023] Figure 6 This is a diagram of the catalytic cycle times of the A1-nano photocatalyst prepared in the examples of the present application. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0025] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0026] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0027] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0028] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0029] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0030] In a first aspect, the present invention provides a method for preparing a nano-photocatalyst, the method comprising:
[0031] The bismuth source ethylene glycol solution is added into the potassium bromide aqueous solution and mixed, and a hydrothermal reaction is carried out at 140-180° C. for 8-20 hours. After separation and collection, a nano photocatalyst is obtained.
[0032] Among them, on the one hand, it can give the nano photocatalyst the ability to inhibit the direct recombination of photogenerated carriers, thereby greatly improving the separation ability of photogenerated electrons and holes, forming hydroxyl radicals and superoxide radicals, and then realizing the efficient degradation of oilfield polymer-containing wastewater; on the other hand, it can introduce oxygen vacancies into the crystal lattice of the compound, so that the Ov-BiOBr nanosheet photocatalyst has anti-photocorrosion performance when degrading oilfield polymer-containing wastewater, and the catalytic activity can still maintain high efficiency after repeated use 30 times. At the same time, the preparation process of this application is simple, the conditions are mild, and it is easy to control, and the purity of the product is high, which has a wide range of industrial application value.
[0033] It should be noted that in the present application, the bismuth source is dissolved in an ethylene glycol solution, potassium bromide is dissolved in an aqueous solution, the two are mixed and then subjected to a hydrothermal reaction, and after the reaction is completed, it is washed with anhydrous ethanol and ultrapure water to remove residual ions, and the resulting precipitate is collected and vacuum dried at 60°C for further use.
[0034] In the embodiment of the present application, the bismuth source is preferably one of bismuth nitrate, bismuth sulfate, bismuth chloride, and bismuth bromide, and more preferably bismuth nitrate. Among them, by selecting these bismuth sources, they are non-toxic or low-toxic, have good response to visible light, are rich in raw materials, and show high catalytic activity and selectivity in various reactions.
[0035] In the embodiment of the present application, the molar ratio of the bismuth source to potassium bromide is preferably 1: 1-1.5, more preferably 1: 1. By controlling the molar ratio of the bismuth source to potassium bromide, oxygen vacancies can be constructed into the Ov-BiOBr nanosheet photocatalyst, which can inhibit the direct recombination of photogenerated carriers, thereby greatly improving the separation ability of photogenerated electrons and holes.
[0036] In the embodiments of the present application, the temperature of the hydrothermal reaction is preferably 140-180°C, more preferably 160°C, and the time is preferably 8-20h, more preferably 12h. Among them, by controlling the temperature and time of the hydrothermal reaction, the reaction rate and the balance of the reaction can be controlled, thereby forming a nanocatalyst with good crystal morphology and high purity. By selecting more optimal reaction conditions, a nano-sheet morphology can be formed, thereby giving it excellent catalytic activity.
[0037] In the embodiment of the present application, the bismuth source ethylene glycol solution is added to the potassium bromide aqueous solution for 80-100 minutes. By controlling the mixing time of the bismuth source ethylene glycol solution and the potassium bromide aqueous solution, the two can be fully mixed, providing a basis for the subsequent further sufficient hydrothermal reaction.
[0038] In a second aspect, an embodiment of the present application provides a nano photocatalyst prepared by the preparation method described in the first aspect, wherein the general chemical formula of the nano photocatalyst is Ov-BiOBr; and the nano photocatalyst is a nanosheet structure.
[0039] It should be noted that the nano photocatalyst prepared in the present application introduces oxygen vacancies into the bismuth oxybromide (BiOBr) photocatalyst to construct an Ov-BiOBr nanosheet structure photocatalyst. Under light conditions, strong oxidizing groups are generated, and many difficult-to-biodegrade oilfield polymer-containing wastewaters can be completely mineralized through free radicals, and the photocatalytic viscosity reduction performance is very significant. At the same time, it has photocorrosion resistance. In the process of photodegradation of oilfield polymer-containing wastewater, after repeated use for 30 times, the catalytic reaction effect has not been significantly reduced, and it has strong photocorrosion resistance. Therefore, the introduction of oxygen vacancies in the nano photocatalyst prepared in the present application not only enhances the photocatalytic performance, but also improves the surface electronic structure of the photocatalyst and enhances its photocorrosion resistance.
[0040] In the third aspect, the embodiment of the present application also provides the application of the nano photocatalyst described in the second aspect in the treatment of oilfield wastewater containing polymers. Based on the excellent photocatalytic performance, light corrosion resistance and structural stability of the prepared nano photocatalyst, the catalytic efficiency can be maintained above 95% after being recycled for 30 times in the treatment of oilfield wastewater containing polymers, and it has a wide application prospect in the treatment of oilfield wastewater containing polymers.
[0041] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0042] Example 1
[0043] This embodiment provides a method for preparing Al-nano photocatalyst (A1-Ov-BiOBr), which specifically includes:
[0044] Add 3.2mmol Bi(NO3)3·5H2O to 21mL ethylene glycol solution and stir at room temperature until completely dissolved to obtain bismuth nitrate ethylene glycol solution;
[0045] Add 3.2 mmol of potassium bromide to 42 mL of distilled water and stir at room temperature until completely dissolved to obtain an aqueous solution of potassium bromide;
[0046] The aqueous solution of potassium bromide was added to the ethylene glycol solution of bismuth nitrate and mixed and stirred for 90 minutes, and hydrothermally treated at 160°C for 12 hours in a 100 mL Teflon-lined stainless steel autoclave, and then naturally cooled to 25°C. The obtained precipitate was collected and washed with anhydrous ethanol and ultrapure water to remove residual ions. Finally, it was vacuum dried at 60°C to obtain the A1-nanophotocatalyst (A1-Ov-BiOBr).
[0047] Example 2
[0048] This embodiment provides a method for preparing A2-nano photocatalyst (A2-Ov-BiOBr), which specifically includes:
[0049] Add 3.0mmol Bi(NO3)3·5H2O to 21mL ethylene glycol solution and stir at room temperature until completely dissolved to obtain bismuth nitrate ethylene glycol solution;
[0050] Add 3.0 mmol of potassium bromide to 42 mL of distilled water and stir at room temperature until completely dissolved to obtain an aqueous solution of potassium bromide;
[0051] The aqueous solution of potassium bromide was added to the ethylene glycol solution of bismuth nitrate and mixed and stirred for 90 minutes, and hydrothermally treated at 160°C for 12 hours in a 100 mL Teflon-lined stainless steel autoclave, and then naturally cooled to 25°C. The obtained precipitate was collected and washed with anhydrous ethanol and ultrapure water to remove residual ions. Finally, it was vacuum dried at 60°C to obtain A2-nanophotocatalyst (A2-Ov-BiOBr).
[0052] Example 3
[0053] This embodiment provides a method for preparing A3-nano photocatalyst (A3-Ov-BiOBr), which specifically includes:
[0054] Add 3.5mmol Bi(NO3)3·5H2O to 21mL ethylene glycol solution and stir at room temperature until completely dissolved to obtain bismuth nitrate ethylene glycol solution;
[0055] Add 3.5 mmol potassium bromide to 42 mL distilled water and stir at room temperature until completely dissolved to obtain an aqueous solution of potassium bromide;
[0056] The aqueous solution of potassium bromide was added to the ethylene glycol solution of bismuth nitrate and mixed and stirred for 90 minutes, and hydrothermally treated at 160°C for 12 hours in a 100 mL Teflon-lined stainless steel autoclave, and then naturally cooled to 25°C. The obtained precipitate was collected and washed with anhydrous ethanol and ultrapure water to remove residual ions. Finally, it was vacuum dried at 60°C to obtain A3-nanophotocatalyst (A3-Ov-BiOBr).
[0057] The nano photocatalysts prepared in the examples of the present application all have similar catalytic performance, and the nano photocatalyst prepared in Example 1 has the best comprehensive performance. Therefore, the photocatalyst prepared in Example 1 is used for further comparative testing.
[0058] At the same time, in order to verify the comprehensive performance of the nano-photocatalyst prepared in the above examples, the present application provides the following comparative examples for detailed description.
[0059] Comparative Example 1
[0060] This comparative example provides a method for preparing a B1-photocatalyst (B1-BiOBr), which specifically includes:
[0061] 2 g of A1-Ov-BiOBr prepared in Example 1 was placed in a muffle furnace, and then heated to 320°C at a heating rate of 5°C / min in an air atmosphere and maintained for 2.5 h. It was washed three times with anhydrous ethanol and ultrapure water. Finally, it was vacuum dried at 60°C to obtain B1-photocatalyst (B1-BiOBr).
[0062] In order to verify the appearance and structure of the prepared A1-Ov-BiOBr and B1-BiOBr, X-ray diffraction, scanning electron microscopy and EPR tests were performed on A1-Ov-BiOBr and B1-BiOBr. The results are shown in the figure. Figure 1-3 shown.
[0063] according to Figure 1 As is known, by performing X-ray diffraction tests on A1-Ov-BiOBr and B1-BiOBr, the XRD patterns of the obtained samples were compared with the standard card (JCPDS card NO.78-03448), which proved the material synthesis of BiOBr and Ov-BiOBr.
[0064] according to Figure 2 As far as we know, the surface morphology of B1-BiOBr was observed by scanning electron microscopy ( Figure 2 a) and the surface morphology of Al-Ov-BiOBr ( Figure 2 b) From Figure 2 (a) It can be seen that the morphology of B1-BiOBr presents a uniform flake structure. Figure 2(b) It can be seen that the surface of Al-Ov-BiOBr also presents a uniform lamellar structure.
[0065] according to Figure 3 As we know, the introduction of oxygen vacancies in A1-nanophotocatalyst and B1-photocatalyst is characterized by EPR spectroscopy. The g value of the material with oxygen vacancies is about 2.00, which is also the diagnostic data of oxygen vacancies. The g value of A1-nanophotocatalyst and B1-photocatalyst nanosheets is 2.003, which has typical oxygen vacancies, and the peak of A1-nanophotocatalyst is sharper than that of B1-photocatalyst. It can be clearly seen that oxygen vacancies are introduced into BiOBr photocatalyst.
[0066] In order to verify the photocatalytic performance of the nano-photocatalyst prepared in the examples of the present application, the steady-state solid fluorescence test was performed on the A1-Ov-BiOBr prepared in the examples of the present application and the B1-BiOBr prepared in the comparative example. The results are as follows: Figure 4 and Figure 5 shown.
[0067] according to Figure 4 As far as we know, solid ultraviolet diffuse reflectance spectroscopy tests were conducted on A1-Ov-BiOBr and B1-BiOBr, and the test results showed that BiOBr has obvious visible light responsiveness when the wavelength is greater than 380nm. After further introducing oxygen vacancies, Ov-BiOBr has an expanded light absorption range, which is conducive to increasing the utilization rate of visible light and thus improving the photocatalytic performance.
[0068] according to Figure 5 As far as we know, solid steady-state fluorescence spectroscopy tests were carried out on A1-Ov-BiOBr and B1-BiOBr. The test results show that the introduction of oxygen vacancies in Ov-BiOBr can produce electron capture states to inhibit the direct recombination of photogenerated carriers, greatly improving the separation ability of photogenerated electrons and holes, thereby greatly enhancing the photocatalytic degradation performance of oilfield polymer-containing wastewater.
[0069] In order to verify the photodegradation effect of oilfield wastewater containing polymer, four groups of experiments were carried out to compare the photodegradation of oilfield wastewater containing polymer using the prepared A1-Ov-BiOBr and B1-BiOBr. The first group used B1-BiOBr to photodegrade oilfield wastewater containing polymer under light conditions, the second group used A1-Ov-BiOBr to photodegrade oilfield wastewater containing polymer under light conditions, the third group used A1-Ov-BiOBr to degrade oilfield wastewater containing polymer under no light conditions, and the fourth group did not add any catalyst. The test results are shown in Table 1.
[0070] The performance evaluation of the photocatalyst was carried out under vertical irradiation of a 300WXe lamp (PLS-SXE300UV, Beijing Bofeilai Co., Ltd.) with a UV cutoff filter (λ≥420nm). 100mL of oilfield polymer-containing wastewater and 10mg of photocatalyst were added to an all-quartz transparent reactor. Before the photocatalytic measurement, the mixed solution was continuously stirred for 60min under dark conditions to reach adsorption-desorption equilibrium. A sample used as a dark control was wrapped in aluminum foil and kept in a dark environment. After the start of the photocatalytic reaction, 3mL of the suspension was taken 30 minutes later, and the concentration of HPAM was determined by a spectrophotometer at a wavelength of 610nm. 8mL was taken for viscosity test of the reaction system.
[0071] Table 1 Catalytic test results
[0072] Serial number catalyst HPAM removal rate System viscosity (mPa / s) Remark 1 BnB 53.3% 3.86 illumination 2 Ov-BiOBr 96.1% 0.63 illumination 3 Ov-BiOBr - 6.71 No light 4 - - 6.72 No light
[0073] According to the test results in Table 1, oxygen vacancies were introduced on the basis of BiOBr with visible light response to construct a new photocatalyst Ov-BiOBr nanosheet, which significantly improved the photodegradation effect of oilfield wastewater containing polymers, and the removal rate of polyacrylamide can reach 96.1%, which is much better than 53.3% of BiOBr. In addition, the viscosity test further verified the superiority of the removal efficiency. After 30 minutes of photodegradation, the viscosity of the system was significantly reduced from 6.72mPa / s to 0.63mPa / s. It shows that Ov-BiOBr nanosheets significantly improve the photodegradation effect of oilfield wastewater containing polymers. According to the test results in Table 1, the efficient photocatalytic performance may come from the introduction of oxygen vacancies, which can produce electron capture states to inhibit the direct recombination of photogenerated carriers, greatly improve the separation ability of photogenerated electrons and holes, and thus greatly enhance the photocatalytic degradation performance of oilfield wastewater containing polymers. Under the conditions of no light and no photocatalyst, the polyacrylamide in the wastewater containing polymers was hardly degraded, proving that the treatment of wastewater containing polymers is a photodegradation process.
[0074] At the same time, the photocatalyst Ov-BiOBr nanosheets were tested for light corrosion resistance, and A1-Ov-BiOBr and B1-BiOBr were used to photodegrade oilfield polymer-containing wastewater. After the reaction, the concentration of bismuth ions in the solution was measured. The experimental results showed that as the reaction time increased, bismuth ions were gradually released into the solution, and the concentration of B1-BiOBr reached 58 mg / L after 60 minutes. For A1-Ov-BiOBr, the Cd concentration in the solution was only 2.6 mg / L after 60 minutes, indicating that the introduction of oxygen vacancies not only enhanced the photocatalytic performance, but also improved the surface electronic structure of the photocatalyst and enhanced its light corrosion resistance.
[0075] In addition, the photocatalyst A1-Ov-BiOBr nanosheets were subjected to a cyclic performance test to photodegrade the polymer-containing wastewater in the oil field. After the reaction was completed, the nanosheets were taken out and tested for photodegradation again. After 30 cycles of use, the catalytic efficiency remained above 95%. The test results are as follows: Figure 6 As shown, it is indicated that the nano photocatalyst prepared in the present application has good structural stability and catalytic stability.
[0076] Therefore, the preparation method provided by the present application is to prepare a photocatalyst of Ov-BiOBr nanosheet structure by adding a bismuth source ethylene glycol solution to an aqueous solution of potassium bromide for hydrothermal reaction. On the one hand, the nanophotocatalyst can be given the ability to inhibit the direct recombination of photogenerated carriers, thereby greatly improving the separation ability of photogenerated electrons and holes, forming hydroxyl radicals and superoxide radicals, and then realizing the efficient degradation of oilfield polymer-containing wastewater; on the other hand, oxygen vacancies can be introduced into the lattice of the compound, so that the Ov-BiOBr nanosheet photocatalyst has anti-photocorrosion performance when degrading oilfield polymer-containing wastewater, and the catalytic activity can still maintain high efficiency after repeated use 30 times. At the same time, the preparation process of the present application is simple, the conditions are mild, and it is easy to control, and the purity of the product is high, which has a wide range of industrial application value.
[0077] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0078] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A method for preparing a nano photocatalyst, characterized in that: The method comprises: The bismuth source ethylene glycol solution is added into the potassium bromide aqueous solution and mixed, and a hydrothermal reaction is carried out at 140-180° C. for 8-20 hours. After separation and collection, a nano photocatalyst is obtained.
2. The method for preparing the nano-photocatalyst according to claim 1, characterized in that: The bismuth source is one of bismuth nitrate, bismuth sulfate, bismuth chloride and bismuth bromide.
3. The method for preparing the nano-photocatalyst according to claim 1, characterized in that: The bismuth source is bismuth nitrate.
4. The method for preparing the nano-photocatalyst according to claim 1, characterized in that: The molar ratio of the bismuth source to potassium bromide is 1:1-1.
5.
5. The method for preparing the nano-photocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160° C. and the time is 12 h.
6. The method for preparing the nano-photocatalyst according to claim 1, characterized in that: The ethylene glycol solution of the bismuth source is added to the aqueous solution of potassium bromide and mixed for 80-100 minutes.
7. A nano photocatalyst prepared according to any one of claims 1 to 6, characterized in that: The nano photocatalyst is a nano sheet structure.
8. Use of the nano-photocatalyst according to claim 7 in the treatment of polymer-containing wastewater in oil fields.